The Linguistics of Spoken Communication in Early Modern English Writing Exploring Bess of Hardwick's Manuscript Letters - Marcus, Imogen (New Approaches to English Historical Linguistics, 2018)
XVIII, 357 p. 16 illus., 10 illus. in color.